THE EFFECT OF THE SNOWBALL THROWING LEARNING MODEL ON STUDENTS' COGNITIVE LEARNING OUTCOMES IN FIFTH-GRADE PANCASILA EDUCATION AT SD NEGERI 040544 DOLAT RAYAT - Purba, Dhea Steviana Br; Tindaon, Juwita; Gule, Yosefo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by low cognitive learning outcomes and limited learning activities among students in Pancasila Education, especially in the topic of norms and rules, which were still dominated by conventional teacher-centered learning. As a result, students tend to be passive and less involved in the learning process. This study aimed to determine the effect of the Snowball Throwing learning model on the cognitive learning outcomes of fifth-grade students in Pancasila Education at SD Negeri 040544 Dolat Rayat in the 2025/2026 academic year. The research used a quantitative approach with a two-group pretest-posttest quasi-experimental design. The sample consisted of 50 students, including 25 in class VA (control group) and 25 in class VB (experimental group), selected using total sampling. The instrument was a multiple-choice learning outcome test with 10 valid items out of 15, and the Cronbach's Alpha reliability coefficient was 0.718. Data were analyzed using descriptive and inferential statistics, including tests of normality, homogeneity, and independent-samples t-tests. The results showed that the posttest mean score of the control class was 61.60, while the experimental class reached 80.80. The t-test showed t=4.487, p=0.000, indicating a significant effect.